2014
DOI: 10.1016/j.jestch.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and analysis of micro-WEDM process of titanium alloy (Ti–6Al–4V) using response surface approach

Abstract: a b s t r a c tMicro-machining technology is effectively used in modern manufacturing industries. This paper investigates the influence of three different input parameters such as voltage, capacitance and feed rate of micro-wire electrical discharge machining (micro-WEDM) performances of material removal rate (MRR), Kerf width (KW) and surface roughness (SR) using response surface methodology with central composite design (CCD). The experiments are carried out on titanium alloy (Tie6Ale4V). The machining chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(30 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…At the end, kerf width is just about linearly proportional to the thickness of the material. Kerf measures the width of material that is removed by a cutting process and further determines the dimensional accuracy of the finished component [24]. During the cutting process, the wire gap varies due to the electrode deflection and spark which may lead to a variation in kerf width.…”
Section: Kerf Widthmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end, kerf width is just about linearly proportional to the thickness of the material. Kerf measures the width of material that is removed by a cutting process and further determines the dimensional accuracy of the finished component [24]. During the cutting process, the wire gap varies due to the electrode deflection and spark which may lead to a variation in kerf width.…”
Section: Kerf Widthmentioning
confidence: 99%
“…Optimization techniques such as design of experiments [9], response surface methodology [10][11][12], fuzzy control system [13][14][15][16][17], genetic algorithm [18] and grey relational analysis [19] are the inevitable tool in achieving optimum process parameters of the wire EDM process. A similar kind of evaluation has also been performed by many researchers on various materials like Inconel [20,21], AISI D2 [22,23], titanium and titanium super alloys [24][25][26][27], etc. Based on the evaluation of those research papers on wire EDM, it has been seen that different attempts are made on the investigations of predicting the effect of process parameters on various conductive materials for achieving maximum material removal rate (MRR), minimum surface roughness (Ra) and wire wear ratio (WWR) on wire EDM and they were found useful.…”
Section: Introductionmentioning
confidence: 99%
“…As of late, the looks into in WEDM demonstrated that aluminum composites gives magnificent reactions in machining application [15]. Thus, associated to current review, an endeavour was performed in exploring the process parameters impact on the reactions like MRR and surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The experiment is conducted with negative electrode potential and according to the L18 Orthogonal Array from Taguchi method and studied the effects of process parameters on EDM performance characteristics namely, Metal Removal Rate (MRR) and Tool Wear Rate (TWR). P. Sivaprakasam et al [10] investigated the influence of three different input parameters such as voltage, capacitance and feed rate of micro-wire electrical discharge machining (micro-WEDM) performances of material removal rate (MRR), Kerf width (KW) and surface roughness (SR) on titanium alloy (Ti6Al-4V) using response surface methodology (RSM) with central composite design (CCD) and Analysis of variance (ANOVA) was used to find out the significant influence of each factor. Found the significant machining results of material removal rate, Kerf width and surface roughness.…”
Section: Introductionmentioning
confidence: 99%